2011
DOI: 10.1002/jrs.3099
|View full text |Cite
|
Sign up to set email alerts
|

Controlled SnO2 nanocrystal growth in SiO2–SnO2 glass‐ceramic monoliths

Abstract: Crack‐free (100–x) SiO2–x SnO2 glass‐ceramic monoliths have been prepared by the sol–gel method obtaining for the first time SnO2 concentrations of 20% with annealing at 1100 °C. Heat‐treatment resulted in the formation and growth of SnO2 nanocrystals within the silica matrices. Combined use of Fourier transform–Raman spectroscopy and in situ high‐temperature X‐Ray diffraction shows that SnO2 particles begin to crystallize in the cassiterite‐type phase at 80 °C and that their average apparent size remains arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…89 No other impurities or tin-oxygen states are observed in the Raman spectrum, although bands attributable to oxygen vacancies, SnO 2 disorder and nanocrystallite dimensions were also observed. [90][91][92][93] However, due to the poor Raman scattering capabilities of SnO 2 , such bands were only observable at higher film thicknesses, corresponding to longer deposition times. Assuming compositional uniformity across the various AA-AP CVD seed-overlay depositions (as opposed to morphological and film thickness differences), it is thought such signals are applicable across all films produced here.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…89 No other impurities or tin-oxygen states are observed in the Raman spectrum, although bands attributable to oxygen vacancies, SnO 2 disorder and nanocrystallite dimensions were also observed. [90][91][92][93] However, due to the poor Raman scattering capabilities of SnO 2 , such bands were only observable at higher film thicknesses, corresponding to longer deposition times. Assuming compositional uniformity across the various AA-AP CVD seed-overlay depositions (as opposed to morphological and film thickness differences), it is thought such signals are applicable across all films produced here.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…As expected, the BET surface areas are significantly lower than that observed for mesoporous SiO 2 prepared by TP of 2,2'-spirobi[4H-1,3,2-benzodioxasiline] (904 m 2 g À1 ), [44] but comparable with the highest values reported for SnO 2 /SiO 2 hybrid materials prepared by the sol-gel process. [66] SiO 2 /SnO 2 materials with tin oxide content of 22 and 29 wt % show surface areas in the range 269-343 m 2 g À1 (heat treatment 700-400 8C) [23] and 375-494 m 2 g À1 (heat treatment 800-400 8C), [67] whereas with increasing tin oxide content of 90 and 75 wt % surface areas of 211-340 m 2 g À1 (heat treatment 600-400 8C) [31] and 133-209 m 2 g À1 (heat treatment 800-400 8C) [30] have been reported. The SiO 2 /SnO 2 materials obtained from the TP show comparatively high surface areas up to 378 m 2 g À1 (700 8C heat treatment) with a tin oxide content of 54 wt %.…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…Notably, long aging times for the preparation of xerogels, which in some cases are several days or even weeks, are not necessary in the TP process. [67,68]…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…A relevant drawback related to SnO 2 NCs is the low solubility of Ln 3+ limited to ~0.05%, the remaining ions being segregated at grain boundaries, probably in the form of Ln 2 Sn 2 O 7 crystals [94]. To overcome this limitation, Van Tran et al [95,96] prepared SiO 2 -SnO 2 GCs with a maximum nominal NCs concentration of 20 mol % to allow for higher Ln 3+ amount incorporation in SnO 2 NCs. The authors prepared Er 3+ -doped materials and PL measurements showed that an increase in SnO 2 concentration promotes Er 3+ ions’ incorporation in SnO 2 NCs.…”
Section: Introductionmentioning
confidence: 99%